Ventral dermatitis in rowi (Apteryx rowi) due to cutaneous larval migrans. Issue 1 (April 2015) - Gartrell, B.D.; Argilla, L.; Finlayson, S.; Gedye, K.; Gonzalez Argandona, A.K.; Graham, I.; Howe, L.; Hunter, S.; Lenting, B.; Makan, T.; McInnes, K.; Michael, S.; et al.
Graphical Abstract